ARDS Weaning: The Impact of Abnormal Breathing Patterns Detected by Electric Tomography Impedance and Respiratory Mechanics Monitoring - Wawrzeniak, Iuri Christmann; Victorino, Josué Almeida; Pacheco, Eder Chaves; Alcala, Glasiele Cristina; Amato, Marcelo Britto Passos; Vieira, Silvia Regina Rios (Respiratory care, 2025)
After the improvement of the initial phase of ARDS, when the patients begin spontaneous breathing and weaning from mechanical ventilation, some patients may present abnormal breathing patterns, whose evaluation of the repercussions were poorly studied. This study proposed to evaluate abnormal breathing patterns through the use of electrical impedance tomography (EIT), and clinical, respiratory mechanics, and ventilatory parameters according to the types of weaning from mechanical ventilation. This was a prospective cohort study of subjects with ARDS who were considered able to be weaned from mechanical ventilation in the clinical-surgical ICU. Weaning types were defined as simple, difficult, and prolonged weaning. EIT, ventilatory, lung mechanics, and clinical data were collected. Data were collected at baseline in a controlled ventilatory mode and, after neuromuscular blocker withdrawal, data were collected after 30 min, 2 h, and 24 h. EIT parameter analysis was performed for ventilation distribution in the lung regions, pendelluft, breath-stacking, reverse-trigger, double-trigger, and asynchrony index. The study included 25 subjects who were divided into 3 groups (9/25 simple, 8/25 difficult, and 8/25 prolonged weaning). The prolonged weaning group showed more delirium, ICU-acquired weakness, stay in ICU, and hospital and ICU mortality. During the change from controlled to spontaneous mode, we observed increased tidal volumes and driving pressures, which were mainly found in the prolonged weaning group when compared with the simple weaning group. The prolonged weaning group showed a higher flow index, more asynchronies during volume-assisted ventilation, a higher incidence of pendelluft, and redistribution of ventilation to posterior regions visualized by EIT. The present study showed abnormal breathing patterns in the prolonged weaning group. The clinical occult findings of abnormal breathing patterns could be monitored, mainly through EIT and with better assessment of pulmonary mechanics.